Kajian Etis Teologis Terhadap Kebiasaan Mowali Di Jemaat Persiapan Koinonia Lontio - Vira Margareta Kalasan; Naftali Kiyuk; Mardian Baali (TEVUNAH: Jurnal Teologi dan Pendidikan Kristen, 2023)
This research explores mowali habits in the Koinonia Lontio Preparatory Congregation regarding Christian teachings about love and forgiveness. The method used in this research is a qualitative method involving 14 informants consisting of members and the Congregation Council. Data was taken using interview techniques and analyzed using reduction, display, and conclusion techniques. The research results show that the mowali habit in the Koinonia Lontio Preparatory Congregation is not in line with Christian teachings about love and forgiveness. The mowali pattern causes a breakdown in relationships with others to share love and shows an unwillingness to forgive. This research implies the importance of proper education and teaching about Christian teachings about love and forgiveness and the need for efforts to change mowali habits that conflict with these teachings.